Comorbidity indices in orthopaedic surgery: a narrative review focused on hip and knee arthroplasty. Issue 8 (10th August 2021) - Sinclair, SaTia T.; Emara, Ahmed K.; Orr, Melissa N.; McConaghy, Kara M.; Klika, Alison K.; Piuzzi, Nicolas S.
Abstract : Comorbidity indices currently used to estimate negative postoperative outcomes in orthopaedic surgery were originally developed among non-orthopaedic patient populations. While current indices were initially intended to predict short-term mortality, they have since been used for other purposes as well. As the rate of hip and knee arthroplasty steadily rises, understanding the magnitude of the effect of comorbid disease on postoperative outcomes has become increasingly more important. Currently, the ASA classification is the most commonly used comorbidity measure and is systematically recorded by the majority of national arthroplasty registries. Consideration should be given to developing an updated, standardized approach for comorbidity assessment and reporting in orthopaedic surgery, especially within the setting of elective hip and knee arthroplasty. Cite this article: EFORT Open Rev 2021;6:629-640. DOI: 10.1302/2058-5241.6.200124